Magma Propagation at Piton de la Fournaise From Joint Inversion of InSAR and GNSS. Issue 2 (16th February 2019) - Smittarello, D.; Cayol, V.; Pinel, V.; Peltier, A.; Froger, J‐L.; Ferrazzini, V.
Abstract: Magma propagation is an unsteady process controlled by magma‐crust interaction. To provide information on its dynamics, we invert complementary ground deformation data spanning the 8 hr preceding the 26 May 2016 eruption at Piton de la Fournaise (PdF) volcano (La Réunion, France). Data are inverted using 3‐D boundary element models combined with a Monte Carlo inversion method. The final geometry of the displacement source is determined based on four interferograms spanning the whole propagation phase while the dynamics of the propagation is inferred from temporal inversion of continuous Global Navigation Satellite System (GNSS) data, using the final geometry as an a priori to constrain the source. The best modeled magma path consists in a 2, 700‐m‐long sill located 800 m above sea level and connected to the eruptive fissure by a subvertical dike. The quick opening of the horizontal part of the intrusion could have been favored by limited flank sliding during the early stage of propagation. The intrusion then stalled for ∼5 hr, while pressure increased slightly, until final upward propagation and eruption. Volume budget suggests that the eruption was fed by a single batch of magma quickly disconnected from its source. The delay prior to the eruption may reflect a limited magma supply. Finally, two mechanisms, potentially acting together, might have favored the eruption: a driving role of magmatic gas and/or, as often observed at Piton de la Fournaise, an eastward flank slip. Plain Language Summary: Basaltic magma stored beneath volcanoes reaches the surface by fracturing the Earth's crust. As experienced in May 2018 at Kilauea volcano (Hawaii, USA), magma can travel kilometers from the reservoir and fissure opening may threaten man‐made structures. Anticipating where and when eruptive fissures open requires better understanding of the factors controlling magma propagation. During the 26 May 2016 eruption of Piton de la Fournaise, Réunion Island, the preeruptive crisis spanned 8hr25min from the first signal recorded by the observatory to the eruption onset.We determine the magma paths and propagation timing, which led to this eruption using complementary satellite data of ground surface displacement, combining radar interferometry, which provides high spatial resolution, with GPS, which provides high temporal resolution. We highlight complex magma propagation within the subareal volcano, showing two direction changes, an arrest and an acceleration. Flank slip and magma degassing seem to play a key role in controlling both the geometry and the timing. Based on this scenario, this event was close to turn into a failed eruption as there was a 5‐hr pause in propagation before magma finally reached the surface. Understanding such unusual eruptions is a challenge for observatories as it may lead to repeated "false" alerts. Key Points: Magma feeding the May 2016 eruption propagated laterally as a sill before turning into a dike The sill propagation is stepwise with an initial acceleration followed by a 5‐hr pause The eruption was fed by a single batch of magma quickly disconnected from its source